Recruiting Practices for Change Initiatives Is Hard: Findings From EvidenceNOW. (May 2018) - Sweeney, Shannon M.; Hall, Jennifer D.; Ono, Sarah S.; Gordon, Leah; Cameron, David; Hemler, Jennifer; Solberg, Leif I.; Crabtree, Benjamin F.; Cohen, Deborah J.
Engaging primary care practices in initiatives designed to enhance quality, reduce costs, and promote safety is challenging as practices are already participating in numerous projects and mandated programs designed to improve care delivery and quality. Recruiters must expand their recruitment tools to engage today's practices in quality improvement. Using grant proposals, online diaries, observational site visits, and interviews with key stakeholders, the authors identify successful practice recruitment strategies in the EvidenceNOW initiative, which aimed to recruit approximately 1500 small- to medium-sized primary care practices. Recruiters learned they needed to articulate how participation in EvidenceNOW aligned with other initiatives and could help practices succeed with federal and state initiatives, recognition programs, and existing or future payment requirements. Recruiters, initiative leaders, and funders must now consider how their efforts align with ongoing initiatives to successfully recruit and engage practices, ease practice burden, and encourage participation in efforts that support practice transformation.